The Drug Business as a Field of Struggle in Turkey. Issue 5 (4th May 2021) - Mercan, Boran Ali
ABSTRACT: The organization of the street-level drug business has been a central concern of many contemporary urban crime ethnographies in the West; however, it has never been researched in Turkey. Addressing the literature gap, this article examines the methods of a local drug enterprise in Ankara through offender-based research. Ethnographic data demonstrates that the local drug trade tends to be structured as a field of struggle in which agents make affective investments and wrestle for material and symbolic rewards, characterized by fast cash and notoriety. Resultantly, two main ranks emerge, of drug enterprise owners and dealers/lookouts. Enterprise owners journey far in their criminal trajectories and thus hold a higher level of street capital dependent on their prestige and infamous reputations. However, lookouts consist of lower-class, disadvantaged youths lacking any experience aside from daring and physical prowess. Their search for recognition and an ethos of criminal cultural consumerism create a potential source of conflict and therefore nourishes the dynamism of the field. Unless the marginalized youths' such psychosocial dynamics are considered, anti-drug policies will go wide of the mark due to their ignorance.